SPATIAL MODEL OF BUILT-IN LAND CHANGE (NDBI) IN LANGSA CITY USING CELLULAR AUTOMATA MARKOV (CA-MARKOV) - Kania Maulia Rizky; Triyatno Triyatno (Universitas Sebelas Maret (UNS), 2025)
The increasing population in Langsa City has caused changes in land use to increase, which is due to the urge to meet the need for housing and other supporting facilities. This makes research on built-up land in Langsa City very important to do, where this study aims to analyse and predict changes in built-up land in Langsa City in 2011, 2017, 2023, and 2035, to provide an overview of changes in built-up land that occur from year to year. In addition, this study also analyses the direction of built-up land policy in Langsa City. The method used in this study is a spatial-based quantitative method with the Cellular Automata Markov approach to create built-up land modelling in Langsa City, and the Analytical Hierarchy Process method to identify variables that influence changes in built-up land in Langsa City. This study produces a map of built-up land changes from 2011 to 2023, showing an increase in built-up land area of 2.417 Ha, which is caused by population growth and regional development factors. In addition, this study also produced a prediction map of built-up land in 2035, which was produced through image interpretation with a kappa index accuracy value of 0,88, which is included in the very good accuracy category. In addition, this study also produced a policy direction for built-up land in Langsa City, which shows the main criteria that are a priority, namely physical conditions with sub-criteria, namely the existence of land that must be far from disaster-prone areas.